La participación ciudadana y la toma de decisiones en el gobierno autónomo descentralizado del cantón Chone provincia de Manabí año 2019 - Mero Cedeño, Julexi Lisbeth (2022)
This study focused on determining the influence of citizen participation in decision-making in the Decentralized Autonomous Government of the Chone canton. For this, the mechanisms used were evaluated, if citizens participate in decision-making and based on the results obtained, you establish strategies that involve the community with the GAD of Chone in relevant public issues. This research focused on using the methods: inductive, deductive, descriptive, analytical and synthetic; techniques such as the observation with which the mechanisms of citizen participation were determined, the interview, carried out with the director of the department under study; On the other hand, the survey was applied to a sample of the Chonense population, obtaining relevant information for this study from both techniques. It was concluded that among the mechanisms used by this municipality are public hearings, empty seats, oversight offices, among others. In the same way, a relevant result is that the majority of the people surveyed do not feel that their opinions are valid, in addition to the fact that the authorities do not provide the information and ease necessary to carry out citizen participation. For this, strategies are proposed that allow greater co-responsibility between the community and the Decentralized Autonomous Government of Chone.